2016
DOI: 10.1016/j.juro.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Concept and Method of Endoscopic Urethral Stricture Treatment Using Liquid Buccal Mucosal Graft

Abstract: This proof of concept study demonstrated the feasibility of using liquid buccal mucosal grafts for endoscopic urethral stricture repair. Such a method may allow for wide application of this novel concept of using liquid buccal mucosal grafts to augment direct vision internal urethrotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Nikolavsky et al . reported a novel method of urethral stricture treatment by injection of autologous liquid buccal mucosa grafts suspended in fibrin glue in combination with DVIU in a rabbit model, suggesting the possibility of endoscopic buccal mucosa cell implantation in urethral wounds . In the present study, Vaddi et al .…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Nikolavsky et al . reported a novel method of urethral stricture treatment by injection of autologous liquid buccal mucosa grafts suspended in fibrin glue in combination with DVIU in a rabbit model, suggesting the possibility of endoscopic buccal mucosa cell implantation in urethral wounds . In the present study, Vaddi et al .…”
supporting
confidence: 49%
“…Nikolavsky et al reported a novel method of urethral stricture treatment by injection of autologous liquid buccal mucosa grafts suspended in fibrin glue in combination with DVIU in a rabbit model, suggesting the possibility of endoscopic buccal mucosa cell implantation in urethral wounds. 4 In the present study, Vaddi et al further advanced this concept and carried out a preliminary study examining the feasibility of a cell-based endoscopic technique using buccal mucosa cells encapsulated in a thermoreversible gelation polymer scaffold in six male patients with bulbar urethral stricture. 5 Although all six patients had a stricture >2-cm long, which are theoretically difficult to be cured by DVIU alone, four of them achieved relatively long-term stricture-free status by this endoscopic technique.…”
mentioning
confidence: 91%
“…Following the inclusion and exclusion criteria, a total of 43 studies were selected for full-text reading ( Figure 1 ). Only 28 studies were considered eligible for quality appraisal [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. These studies comprise a range of approaches and scaffolds for urethral repair in rabbits, which are summarized in the Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Reconstruction of local anatomic disorder and function might be an alternative approach to cure esophageal restenosis. As recommended, oral mucosal transplantation is an effective technique for treating ureteral or urethral strictures [5,12]. There have been no reports of mucosal grafting to treat esophageal strictures, although gastric mucosal transplantation has been introduced to prevent esophageal stricture after circumferential ESD with promising results [13].…”
Section: Discussionmentioning
confidence: 99%